PENGUATAN KETERAMPILAN PUBLIC SPEAKING MELALUI PELATIHAN KHITOBAH BAGI SANTRI MA AL-MUAYYAD SURAKARTA - Dewi, Fitri Ana Ika; Wulandari, Maria; Sabariyanto, Sabariyanto; Santoso, Rochmat Budi; Pratama, Ikke Dewi; Safitri, Linda (LPPM Universitas Nusa Mandiri, 2026)
Public speaking skills in the context of khitobah are essential for students to support educational and da’wah activities. Students of MA Al-Muayyad Surakarta possess good potential due to their religious knowledge. However, challenges remain, including limited understanding of khitobah techniques, lack of confidence, and anxiety, compounded by the absence of regular practice. This community service program aims to provide reinforcement of students’ public speaking skills through khitobah training. The program involved problem sidentification, training, and evaluation using a service learning approach that integrates material delivery and direct practice. The achievement of the training program was evaluated through questionnaires and interviews to obtain an overview of participants’ responses and perceptions. The results indicate positive responses, with 84.2% of participants feeling assisted in understanding concepts and techniques, 79.9% reporting greater confidence, and 84.8% feeling more capable of managing nervousness. Interviews also suggest perceived benefits in self-confidence and readiness to perform. Overall, the training contributes positively to students’ readiness to engage in public speaking activities in both school and community contexts.